EFFECT OF DIFFERENT PRESERVATIVES ON THE HUMAN SOFT TISSUES STORED AT DIFFERENT TEMPERATURES AND INTERVALS OF TIME FOR THE ISOLATION OF DNA FOR DNA FINGERPRINTING (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
The major problem faced by the forensic laboratories is to get the samples in proper conditions. Most of the  biological samples brought for DNA analysis are either partially degraded or completely degraded and many a  times it is not possible to extract DNA from them. It necessitates the optimization of the temperature conditions  and preservatives for the storage of the biological samples (soft tissues). Our study concluded that -80°C  temperature and normal saline as preservative is the best combination for the storage of the forensic samples till  processed further. Since –80°C facility is not available in all the labs, the samples stored in normal saline at  lower temperature (4°C) is found to be the feasible condition for long storage. Formalin fixation of the samples  for long storage is not desirable for the isolation of DNA because first it has to be deformalized and also it  hampers the PCR activity.
Keywords: DNA fingerprinting; Preservatives